Directing positional specificity in enzymatic synthesis of bioactive 1‐phosphatidylinositol by protein engineering of a phospholipase D. Issue 1 (4th September 2015) - Damnjanović, Jasmina; Kuroiwa, Chisato; Tanaka, Hidetoshi; Ishida, Ken; Nakano, Hideo; Iwasaki, Yugo
ABSTRACT: Phosphatidylinositol (PI) holds a potential of becoming an important dietary supplement due to its effects on lipid metabolism in animals and humans manifested as a decrease of the blood cholesterol and lipids, and relief of the metabolic syndrome. To establish an efficient, enzymatic system for PI production from phosphatidylcholine and myo ‐inositol as an alcohol acceptor, our previous study started with the wild‐type Streptomyces antibioticus phospholipase D (SaPLD) as a template for generation of PI‐synthesizing variants by saturation mutagenesis targeting positions involved in acceptor accommodation, W187, Y191, and Y385. The isolated variants generated PI as a mixture of positional isomers, among which only 1‐PI exists in nature. Thus, the current study has focused to improve positional specificity of W187N/Y191Y/Y385R SaPLD (NYR) which generates PI as a mixture of 1‐PI and 3‐PI in the ratio of 76/24, by subjecting four residues of its acceptor‐binding site to saturation mutagenesis. Subsequent screening pointed at NYR‐186T and NYR‐186L as the most improved variants producing PI with a ratio of 1‐/3‐PI = 93/7 and 87/13, respectively, at 37°C. Lowering the reaction temperature further improved the specificity of both variants to 1‐/3‐PI > 97/3 at 20°C with no change in total PI yield. Structure model analyses imply that G186T and G186L mutations increased rigidity of the acceptor‐binding site, thus limiting the possible orientations of myo ‐inositol. The two newly isolated PLDs are promising for future application in large‐scale 1‐PI production. Biotechnol. Bioeng. 2016;113: 62–71. © 2015 Wiley Periodicals, Inc. Abstract : Aiming to synthesize bioactive 1‐phosphatidylinositol (1‐PI) as the only positional isomer of PI in a phospholipase D mediated reaction the authors targeted residues of the enzyme's acceptor‐binding site for mutagenesis. Isolated G186T and G186L variants generated 1‐PI almost exclusively (>97% at 20°C). The result came after 2‐way rigidification of the acceptor‐binding site: (1) cavity filling by replacement of Gly with larger residues having different interaction networks and, (2) lowering the reaction temperature.